Li Ion Diffusivity and Improved Electrochemical Performances of the Carbon Coated LiFePO4 - Park, ChangKyoo; Park, Sung Bin; Oh, Si Hyung; Jang, Ho; Cho, Won Il (WILEY-V C H VERLAG GMBH, 2011)
This study examines the effects of a carbon coating on the electrochemical performances of LiFePO4. The results show that the capacity of bare LiFePO4 decreased sharply, whereas the LiFePO4/C shows a well maintained initial capacity. The Li ion diffusivity of the bare and carbon coated LiFePO4 is calculated using cyclic voltammetry (CV) to determine the correlation between the electrochemical performance of LiFePO4 and Li diffusion. The diffusion constants for LiFePO4 and LiFePO4/C measured from CV are 6.56 x 10(-16) and 2.48 x 10(-5) cm(2) s(-1), respectively, indicating considerable increases in diffusivity after modifications. The Li ion diffusivity (D-Li) values as a function of the lithium content in the cathode are estimated by electrochemical impedance spectroscopy (EIS). The effects of the carbon coating as well as the mechanisms for the improved electrochemical performances after modification are discussed based on the diffusivity data.
Keywords: CATHODE MATERIAL; PHOSPHO-OLIVINES; LITHIUM; FE